Application of biosolids to soil affects Cu and Zn accumulation and antioxidant activity of lettuce (Lactuca sativa L.). (28th January 2016) - Haghighi, Maryam; Teixeira da Silva, Jaime A.
Abstract: The application of biosolids to agricultural fields is becoming increasingly common. The effect of biosolids on the behavior of metals in different plants has been reported to be variable and ambiguous. A greenhouse experiment was conducted on a soil spiked with four rates of copper (Cu) (0, 50, 100, and 150 mg kg −1 ) and zinc (Zn) (0, 150, 300, and 450 mg kg −1 ) in lettuce culture. When Cu and Zn were spiked to anaerobically-digested biosolids, their availability in lettuce increased. Root and shoot fresh weight decreased due to a decrease in photosynthetic rate. superoxide dismutase (SOD) and peroxidases (POD) activity increased after the application of Cu and Zn. The bioavailability of Zn in lettuce was greater than that of Cu because of a higher transfer factor in plants and due to a higher endogenous Zn concentration.These results will allow for better fertilization management when biosolids are applied to tomato culture.